Keys for effective multistakeholder science committees: The importance of structure, processes and desired behaviours - Garry Scrimgeour; Kelly Munkittrick; Frederick Wrona; Mark McMaster (Ecological Solutions and Evidence, 2025)
Abstract Multistakeholder Science Committees (MSC's) are increasingly used to inform science assessments and syntheses supporting the development of environmental regulations and policies. By bringing together a diversity of pertinent rights holders and stakeholders they can create holistic and inclusive outcomes that would not otherwise be produced if participants are drawn from a narrow range of expertise and jurisdictional representation. However, MSC's also create notable challenges. As practitioners and leaders of a multitude of MSC's, we draw from our collective experiences to identify key steps we feel will ensure high performance of MSC's. We highlight the importance of recognizing the mandate letter and developing a jointly agreed‐upon Terms of Reference (TOR) and then identifying specific aspects related to: (i) roles and responsibilities of participants; (ii) founding principles required to enable the work of a MSC; (iii) acceptable behaviours for MSC members; and (iv) mechanisms to assess the consequences when undesired behaviours and actions are displayed. We also identify actions and behaviours that will most likely result in the failure of the MSC. Practical implication: The ability to diagnose the underlying causes of challenges to MSC's performance, provides opportunities to resolve them so that the performance can be improved and undesirable actions and behaviours are minimized or avoided.